2016
DOI: 10.1038/ncomms13153
|View full text |Cite
|
Sign up to set email alerts
|

Giant Kerr response of ultrathin gold films from quantum size effect

Abstract: With the size of plasmonic devices entering into the nanoscale region, the impact of quantum physics needs to be considered. In the past, the quantum size effect on linear material properties has been studied extensively. However, the nonlinear aspects have not been explored much so far. On the other hand, much effort has been put into the field of integrated nonlinear optics and a medium with large nonlinearity is desirable. Here we study the optical nonlinear properties of a nanometre scale gold quantum well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 40 publications
1
89
0
1
Order By: Relevance
“…As the thickness of films approach just a few monolayers, the strong confinement could lead to quantum effects that could greatly enhance light–matter interactions . For example, it has recently been reported that the Kerr nonlinear optical response in thin Au films is several orders of magnitude larger than the bulk counterpart . In addition, these films are expected to be more sensitive to external electrical and optical perturbations, making them an attractive material platform for realizing dynamic nanophotonic and plasmonic applications.…”
Section: Introductionmentioning
confidence: 99%
“…As the thickness of films approach just a few monolayers, the strong confinement could lead to quantum effects that could greatly enhance light–matter interactions . For example, it has recently been reported that the Kerr nonlinear optical response in thin Au films is several orders of magnitude larger than the bulk counterpart . In addition, these films are expected to be more sensitive to external electrical and optical perturbations, making them an attractive material platform for realizing dynamic nanophotonic and plasmonic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays thin gold films are an important component of highly efficient photonic and plasmonic devices . Ultrathin gold films (thickness < 10 nm) have recently attracted a great deal of interest both for the development of flexible transparent electrodes for optoelectronic devices including thin‐film solar cells, displays and touchscreens, photodetector and light emitting diodes, and for studying quantum‐size effects in metal films . Certainly, high‐quality ultrathin films are also the key element of plasmonic waveguides and hyperbolic metamaterials …”
mentioning
confidence: 99%
“…The n 2 is (8.9−1.6 i ) × 10 −13 m 2 W −1 , which is several orders of magnitude higher than that of traditional nonlinear materials, [ 20 ] and is the direct evidence of ISBTs, as has been demonstrated in gold MQWs. [ 16 ] The ISBT selection rule, if not broken, gives the n 2 a sin(θ) dependence; for example, the n 2 at θ = 10° is expected to be 27% of that at θ = 40°. However, from the measured wavelength dependence of n 2 at θ = 10° (Figure 4c), we observe that it is about 50% of the amplitude of that at θ = 40°, indicating a significant break of the ISBT selection rule.…”
Section: Resultsmentioning
confidence: 99%
“…It was not until very recently, however, that the optical nonlinearities of MQWs have been experimentally explored, enabled by the success in fabrication of ultrathin continuous metallic films on top of a dielectric substrate. [ 13,16,17 ] Surprisingly, ISBT peaks, the signature of the quantum size effect in QWs, have been observed in the nonlinear coefficient spectra of these MQWs [ 16,17 ] ; the manifestation of the ISBTs is an extraordinary enhancement of these optical nonlinearities which are several orders of magnitude larger than those of traditional nonlinear materials at visible/near‐infrared (NIR) frequencies. However, no systematic study of the ISBT selection rules for optical nonlinearities in MQWs has been made.…”
Section: Introductionmentioning
confidence: 99%